2003
DOI: 10.1084/jem.20030630
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Cytokine mRNAs Mark Natural Killer (NK) and NK T Cells Poised for Rapid Effector Function

Abstract: Natural killer (NK) and NK T cells are tissue lymphocytes that secrete cytokines rapidly upon stimulation. Here, we show that these cells maintain distinct patterns of constitutive cytokine mRNAs. Unlike conventional T cells, NK T cells activate interleukin (IL)-4 and interferon (IFN)-γ transcription during thymic development and populate the periphery with both cytokine loci previously modified by histone acetylation. Similarly, NK cells transcribe and modify the IFN-γ gene, but not IL-4, during developmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
491
1
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 546 publications
(518 citation statements)
references
References 27 publications
21
491
1
5
Order By: Relevance
“…How iNKT cells from unsensitized mice produce cytokines so rapidly when activated is unclear. However, the observation that resting iNKT cells have high levels of IL-4 and IFNγ mRNAs provides one potential mechanism [28,29]. Acquisition of this phenotype is a likely consequence of their unique mode of selection in the thymus, because CD4 T cells positively selected by MHC class-II expressed on thymocytes share similar effector functions [30].…”
Section: Cytokine and Chemokine Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…How iNKT cells from unsensitized mice produce cytokines so rapidly when activated is unclear. However, the observation that resting iNKT cells have high levels of IL-4 and IFNγ mRNAs provides one potential mechanism [28,29]. Acquisition of this phenotype is a likely consequence of their unique mode of selection in the thymus, because CD4 T cells positively selected by MHC class-II expressed on thymocytes share similar effector functions [30].…”
Section: Cytokine and Chemokine Productionmentioning
confidence: 99%
“…Further studies will be required to understand the transcriptional regulation of cytokine production by iNKT cells. Epigenetic changes in chromatin structures at the IL-4 and IFNγ loci are known to occur during iNKT cell development in the thymus [29]. It was reported that Notch signaling might control the activity of an enhancer located downstream of the IL-4 locus that is responsible for the initial IL-4 expression in iNKT cells [45].…”
Section: Cytokine and Chemokine Productionmentioning
confidence: 99%
“…Real-time in vivo imaging in the liver should also be valuable for visualizing anti-parasite immunity in context. The development of many mouse strains that produce fluorescent cell lines, such as myelomonocytic cells 21 , dendritic cells 22 or natural killer cells 23 , will help to dissect the role of these cell types during parasitic infection. Similar approaches should also permit illumination of how protective immunity is achieved and how activated T cells interact with infected hepatocytes, or comparison of immune effectors against parasites in naïve or vaccinated animals.…”
Section: Anticipated Resultsmentioning
confidence: 99%
“…One possible explanation is that activation with cytokines induces epigenetic changes at certain cytokine loci, similar to what has been described for memory induction and maintenance in T cells (Youngblood et al 2013). NK cells are already poised for rapid IFN-γ production with constitutive production of mRNA transcripts (Stetson et al 2003), so the question remains as to whether epigenetic modification at the Ifng locus would impact the generation of these memory-like NK cells. Epigenetic regulation could, however, provide a plausible explanation for why the progenies of the cytokine-activated NK cells also exhibit enhanced functions (Cooper et al 2009).…”
Section: Cytokine-driven Memory-like Nk Cells In Micementioning
confidence: 90%